PHYSICAL BASIS OF SOLAR PHOTOVOLTAIC CELLS - Fozilova Mohira Soyibjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Solar photovoltaic (PV) cells are devices that convert sunlight directly into electricity through the photovoltaic effect. This process involves the generation of electron-hole pairs in semiconductor materials, followed by their separation and movement under the influence of an electric field, leading to the flow of electric current. The efficiency of PV cells depends on several factors, including the properties of the semiconductor material, the structure of the p-n junction, and the management of energy losses such as recombination and thermal losses. Silicon-based materials are the most commonly used in PV technology, though alternative materials like thin-film, perovskite, and organic photovoltaics are being explored for their potential to improve efficiency and reduce costs. This article explores the fundamental physical principles underlying solar photovoltaic cells, including the photovoltaic effect, semiconductor behavior, and the challenges related to improving cell efficiency. As research advances, the performance and applicability of PV technology continue to grow, contributing to the broader transition toward renewable energy sources.